Economic burden of acute kidney injury in children and adults: a protocol for a systematic review and meta-analysis - Sean M Bagshaw; Catherine Morgan; Rashid Alobaidi; Emma Heydari Ulrich; Aspen Lillywhite; Michael Paulden; Michael Zappitelli (BMJ Open)
Introduction Acute kidney injury (AKI) is common in hospitalised adults and children and is associated with significantly increased mortality and worse short-term and long-term outcomes. This systematic review and meta-analysis will evaluate the cost associated with AKI.Methods and analysis This health economic analysis will be performed using systematic search of databases, including MEDLINE, EMBASE, CINAHL, Scopus and Cochrane Library from 2009 to the present (search completed on 27 May 2024). Two reviewers will independently complete study selection, data extraction and bias assessment. Inclusion criteria will be randomised controlled trials (RCTs) and observational studies (cohort or case–control) from all countries of hospitalised adults and children. The exposure will be AKI based on definitions using serum creatinine and/or urine output criteria, relative to patients without AKI. The primary outcome studied will be the cost of index hospitalisation associated with AKI episode. Other secondary outcomes will include the cost of intensive care unit admission during index hospitalisation, direct costs related to inpatient and outpatient care) and indirect (time) costs related to loss of productivity. Pooled random-effect meta-analysis ORs with 95% CIs will be reported.Ethics and dissemination Ethics approval was not required due to study methodology. The authors have no competing interests to report. The results will be disseminated in peer-reviewed publications according to guidelines by the Cochrane and Centre for Reviews and Dissemination.PROSPERO registration number CRD42024512658.